THE RELATIONSHIP BETWEEN SELF-REPORTED AND CLINICIAN RATED ASSESSMENT OF DEPRESSION IN CLINICALLY DEPRESSED PATIENTS: Self-Reported and Clinician Assessment of Depression - Qayyum, Rashid; Siddiqui, Salma (Pakistan Armed Forces Medical Journal, 2016)
Objective: The study examines the relationship between a clinician rated measure Hamilton Rating Depression Scale (HRSD) and indigenously developed self-reported Siddiqui-Shah Depression Scale (SSDS) in clinically depressed and matched control group. Study Design: Correlational design. Place and Duration of Study: Data was collected over a span of 6 month from Department of Psychiatry Pakistan Naval Ship (PNS) Shifa Karachi and Combined Military Hospital (CMH) Malir, Karachi Material and Methods: A purposive sample of forty-seven patients from psychiatry department and thirty-six participants in the matched group were first screened on DSM-IV criteria independently by a psychologist, and then assessed on HRSD by the psychiatrist followed by assessment of depression on SSDS by the participants. Results: SSDS has significant relationship with HRSD for both matched group (r=.74, p<.001) and depressed group (r=.38, p<.01). SSDS also indicates moderate sensitivity index (.79) and a significant specificity index (.89). Conclusion: Self-report measure (SSDS) correlates significantly with clinician rated assessment measure (HRSD); it also demonstrates psychometric properties to be recommended for screening depression in general practice.